2020
DOI: 10.1108/jbim-05-2019-0198
|View full text |Cite
|
Sign up to set email alerts
|

Understanding incubation during foreign market entry: lessons learnt from an illustrative Danish case study

Abstract: Purpose This paper aims to discuss business incubation to enter foreign markets in Brazil, Russia, India and China (BRIC) countries through the lens of an “international business incubator” (IBI). International market expansion offers huge opportunities for companies to increase their revenue, but there are also challenging tasks such as the establishment of a business company and the occupation of a strategic position abroad. Practitioners consider this process as the act of incubation, but the theoretical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…, 2021). Via the approach of triangulation from various reports and literature as employed in other studies (Adderley, 2021; Chayer and Lunsford, 2018; Gretzinger et al. , 2022; Cozmiuc and Petrisor, 2020; Salabarria et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021). Via the approach of triangulation from various reports and literature as employed in other studies (Adderley, 2021; Chayer and Lunsford, 2018; Gretzinger et al. , 2022; Cozmiuc and Petrisor, 2020; Salabarria et al.…”
Section: Methodsmentioning
confidence: 99%
“…Triangulation also has been viewed as a research strategy to test validity through the convergence of information from different sources (Hancock et al, 2021). Via the approach of triangulation from various reports and literature as employed in other studies (Adderley, 2021;Chayer and Lunsford, 2018;Gretzinger et al, 2022;Cozmiuc and Petrisor, 2020;Salabarria et al, 2020), we found that our descriptive analysis, identified theme and its subsequent implications which were found and addressed by the conceptual framework, were all reliable and valid evidenced in other field literature and several reports of 2019-2021.…”
Section: Imr 405mentioning
confidence: 99%
“…Blackburne and Buckley also briefly referred to the institutional aspects of the IBI, asserting that it represents a mediating approach during international market entry that can compensate for institutional voids surrounding risk, knowledge, and commitment by providing information, learning, and gradual surmounting of the challenges of foreignness, newness 39 , and outsidership 40 . The institutional aspects were then one of the main subjects of an in-depth analysis performed by Gretzinger et al 41 While Blackburne and Buckley considered the IBI as only an organization, Gretzinger et al 42 regarded it as both an organization and an institution organized around the integration of new enterprises into foreign markets. Applying both network perspective and institutional theory, the authors defined IBI as "an actor with an own organizational structure in a specific institutional setting that takes over various activities to support the company's market entry" 43 .…”
Section: The Ibi As An Entry Modementioning
confidence: 99%